VVI Pacing with Normal QRS duration and Ventricular Function: MOST Trial Findings Relevant to Leadless Pacemakers - Loring, Zak (Pacing Clin Electrophysiol, 2020)
BACKGROUND: Leadless pacemakers (LPs) provide ventricular pacing without the risks associated with transvenous leads and device pockets. LPs are appealing for patients who need pacing, but do not need defibrillator or cardiac resynchronization therapy. Most implanted LPs provide right ventricular pacing without atrioventricular synchrony (VVIR mode). The Mode Selection Trial in Sinus Node Dysfunction Trial (MOST) showed similar outcomes in patients randomized to dual chamber (DDDR) vs ventricular pacing (VVIR). We compared outcomes by pacing mode in LP-eligible patients from MOST. METHODS: Patients enrolled in the MOST study with an LVEF >35%, QRSd <120ms and no history of ventricular arrhythmias or prior implantable cardioverter defibrillators were included (LP-eligible population). Cox proportional hazards models were used to test the association between pacing mode and death, stroke or heart failure hospitalization and atrial fibrillation (AF). RESULTS: Of the 2,010 patients enrolled in MOST, 1,284 patients (64%) met inclusion criteria. Baseline characteristics were well balanced across included patients randomized to DDDR (N=630) and VVIR (N=654). Over four years of follow-up, there was no association between pacing mode and death, stroke or heart failure hospitalization (VVIR HR 1.28 [0.92–1.75]). VVIR pacing was associated with higher risk of AF (HR 1.32 [1.08–1.61], p=0.007), particularly in patients with no history of AF (HR 2.38 [1.52–3.85], p<0.001). CONCLUSION: In patients without reduced LVEF or prolonged QRS duration who would be eligible for LP, DDDR and VVIR pacing demonstrated similar rates of death, stroke or heart failure hospitalization; however, VVIR pacing significantly increased the risk of AF development.